Análise química de cultivares de morango em diferentes sistemas de cultivo e épocas de colheita - Bordignon Júnior, Celso Luiz (2008)
The growth in the production of strawberries requires the use of new technologies. These are the different production systems, aiming to increase the quality and productivity of fruits. The quality of the fruit respect of various parameters, including the content of phenolic compounds, especially the class of anthocyanins, which give the intense red fruit and have great potential antioxidant. This study aimed to assess the phenolic composition of different cultivars in different systems of cultivation and harvest period. To achieve this goal the work was divided into three experiments. In the first pH was determined that best represents the level of anthocyanins in the fruits of strawberry cv. Oso Grande, using spectroscopic methods. Treatments consisted of the following for pH 1.0, 3.0, 4.5; 7.0; 9.0, 13.0. In the second experiment was determined the content of phenolic compounds in four cropping systems and three harvest period, and the treatments (system of cultivation and harvest period) were arranged in a 4 x 3 factorial. The data were analyzed in split plot in time, where the main plot and subplot systems consisted of the seasons. In the third study, was evaluated the content of phenolic compounds in different cultivars and harvest period. In this, the treatments consisted of thirteen and three cultivars harvest period, analyzed the same way that the experiment two. The results in the three trials were submitted to the analysis of variance and differences compared by Tukey test of the 5% significance. The data indicate that the first experiment to extract greater efficiency with the anthocyanins, must be used extrativas solutions at pH 1, because it provides a profile analysis by the classic by ultraviolet spectroscopy. The second work shows that the systems in conventional horizontal bags, as well as the proximity of summer increases the levels of the compounds evaluated. Analyzing the cultivars in the third experiment, it is clear that the cultivars of days neutral Verão and Sielva and cultivar of short days Tudla have high levels of the compounds. As the harvest period, there is the same behavior of the second experiment, except for cultivating Diamante showed that levels constant over the harvests